Severe thyrotoxicosis in an infant revealing familial nonautoimmune hyperthyroidism with a novel (C672W) stimulating thyrotropin receptor germline mutation. Issue 12 (25th October 2017) - Oliver‐Petit, Isabelle; Savagner, Frédérique; Grunenwald, Solange; Vialon, Magaly; Edouard, Thomas; Caron, Philippe
Key Clinical Message: We describe severe thyrotoxicosis in young members of a family with nonautoimmune hyperthyroidism caused by a C672W germline mutation in exon 10 of TSHR gene. In this family, lack of genotype‐phenotype correlation and anticipation across generations could be linked to an increased iodine intake as recently observed in France. Abstract : We describe severe thyrotoxicosis in young members of a family with nonautoimmune hyperthyroidism caused by a C672W germline mutation in exon 10 of TSHR gene. In this family, lack of genotype‐phenotype correlation and anticipation across generations could be linked to an increased iodine intake as recently observed in France.